Penataan Dan Penyimpanan Dokumen Perjalanan Dinas Di Lingkungan Bpkp Dalam Rangka Pembayaran Biaya Perjalanan Dinas - Salwa, Salwa; Mustofa, Anwar; Onida Sinaga, Mawarta; Widhi Sugianingsih, Ni Made; Ginting, Riskon (Publikasi Indonesia, 2025)
This study aims to evaluate the organization and storage of official travel documents within the Financial and Development Supervisory Agency (BPKP) to ensure effective payment processes for travel expenses. A descriptive qualitative method was employed, collecting data through interviews, observations, and document review. Findings reveal key issues such as disorganized storage space, document duplication, and lack of integrated digital systems. As a result, verification and payment processes are time-consuming and error-prone. The discussion highlights that implementing electronic document management systems, staff training, and standardized procedures can accelerate payments while enhancing accountability and transparency. In conclusion, systematic and digitized document organization and storage at BPKP significantly streamline official travel expense payments.